EKSPLORASI KERAGAMAN PLASMA NUTFAH PADI LOKAL KUANTAN SINGINGI BERDASARKAN MORFOLOGI GABAH DAN BERAS - Ezward, Chairil; Suliansyah, Irfan; Rozen, Nalwida; Dwipa, Indra (Jurnal Agroteknologi, 2024)
Farmers in specific region can play a crucial role in preventing the extinction of rare rice varieties by maintaining their commitment to local rice production. This not only contributes to the economic stability of the community but also necessitates exploration efforts to identify and gather specific plant species at risk of extinction. This study employs a descriptive research design to identify, gather, and compare the relationships between local rice genotypes in the Kuantan Singingi regency. The survey method utilizes a planned sample of rice seeds.The exploration process involves observing geographic coordinate locations, collecting local rice seeds, and examining grain and rice morphology based on Bioversity International, IRRI, and WARDA standards from 2007. The Kuantan River, with an altitude ranging from 28.95 to 61.56 meters above sea level, is prone to frequent flooding. A morphological study of grains reveals that, out of 26 local rice genotypes, one pair exhibits the highest similarity rate of 71% when compared to more diverse types. Notably, the white sironda rice from Pulau Madina village in Kuantan Hilir district and pandan wangi rice from Pauh Angit village in Pangean district are identified as the most identical genotypes. By identifying and preserving unique and highly-potential indigenous rice genotypes, this research significantly contributes to the enhancement of food stability, rural economy, and genetic resilience of rice plasma in Indonesia.